The Geopolitics of Java in the 17th Century: A Case Study of Mataram Sultanate - Surya, Riza Afita; Nirmala Puji, Rully Putri (History Department, Semarang State University and Historian Society of Indonesia, 2024)
Abstract: Java Island had long played a significant part both in Southeast Asia and the Pacific region. Between the 16th and 17th centuries, there was a series of political forces took place on the island, from the Hindu-Buddhist Majapahit Kingdom to the rise of Islamic kingdoms. Mataram is being one of the greatest Islamic kingdoms that ever existed in Java. In the 17th century, the Mataram Sultanate began conquering extensive areas of Central and East Java. Thus, it resulted in the shift of political power from the north coast of Java to the hinterland area. Mataram, during the Sultan Agung era, obtained firm relations with coastal areas and forged many marriage alliances. Thus, the Sultanate had access to other cultural traditions besides those of east Java. Eventually, Central Java under the Mataram realm became the centre of geopolitics and Javanese culture. However, after the Dutch company, aka VOC, appeared, the political disruption began. The seventeenth century in Java was mainly between VOC and Javanese and Chinese in a small part, while events in Java were primary concerns for VOC. Mataram, in particular, was a far larger kingdom than any the VOC had invaded, and it obtained a considerable interior where VOC naval power could be said meaningless. This paper presents a chronological framework of how Mataram under Sultan Agung successfully placed Central Java as the geopolitics of Java in the 17th century.Abstrak: Pulau Jawa telah lama memainkan peran penting baik di Asia Tenggara maupun kawasan Pasifik. Antara abad ke-16 dan ke-17, terjadi serangkaian kekuatan politik di pulau tersebut, dari Kerajaan Majapahit yang beragama Hindu-Buddha hingga munculnya kerajaan-kerajaan Islam. Mataram merupakan salah satu kerajaan Islam terbesar yang pernah ada di Jawa. Pada abad ke-17, Kesultanan Mataram mulai menaklukkan wilayah yang luas di Jawa Tengah dan Jawa Timur. Dengan demikian, terjadi pergeseran kekuatan politik dari pesisir utara Jawa ke daerah pedalaman. Mataram, pada masa Sultan Agung, menjalin hubungan yang erat dengan daerah pesisir dan menjalin banyak aliansi perkawinan. Dengan demikian, Kesultanan tersebut memiliki akses ke tradisi budaya lain selain Jawa Timur. Akhirnya, Jawa Tengah di bawah wilayah Mataram menjadi pusat geopolitik dan budaya Jawa. Namun, setelah perusahaan Belanda, alias VOC, muncul, kekacauan politik pun dimulai. Abad ke-17 di Jawa sebagian besar merupakan masa antara VOC dan orang Jawa serta sebagian kecil orang Tionghoa, sementara peristiwa-peristiwa di Jawa merupakan perhatian utama bagi VOC. Mataram, khususnya, merupakan kerajaan yang jauh lebih besar daripada kerajaan mana pun yang pernah diserbu VOC, dan memperoleh wilayah pedalaman yang cukup luas di mana kekuatan angkatan laut VOC dapat dikatakan tidak berarti. Tulisan ini menyajikan kerangka kronologis tentang bagaimana Mataram di bawah Sultan Agung berhasil menempatkan Jawa Tengah sebagai geopolitik Jawa pada abad ke-17.